2019
DOI: 10.1103/physreve.100.022607
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium probability flux of a thermally driven micromachine

Abstract: We discuss the non-equilibrium statistical mechanics of a thermally driven micromachine consisting of three spheres and two harmonic springs [Y. Hosaka et al., J. Phys. Soc. Jpn. 86 (2017)]. We obtain the non-equilibrium steady state probability distribution function of such a micromachine and calculate its probability flux in the corresponding mode space. The resulting probability flux can be expressed in terms of a frequency matrix that is used to distinguish between a non-equilibrium steady state and a ther… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…The competition between the swimmer size and the characteristic length scale associated with the fluid internal structure gives rise to the rich dynamics [21,22]. The present authors have also proposed a generalized three-sphere microswimmer model in which the spheres are connected by two harmonic springs, i.e., an elastic microswimmer [23][24][25][26]. It has been shown that an elastic microswimmer in a purely viscous fluid exhibits "viscoelastic" effects as a whole [23,24].…”
Section: Introductionmentioning
confidence: 91%
“…The competition between the swimmer size and the characteristic length scale associated with the fluid internal structure gives rise to the rich dynamics [21,22]. The present authors have also proposed a generalized three-sphere microswimmer model in which the spheres are connected by two harmonic springs, i.e., an elastic microswimmer [23][24][25][26]. It has been shown that an elastic microswimmer in a purely viscous fluid exhibits "viscoelastic" effects as a whole [23,24].…”
Section: Introductionmentioning
confidence: 91%
“…[67] and analytically in Refs. [68] and [69]. A generalization of the BG model for a system of two coupled noisy Kuramoto oscillators, i.e., oscillators coupled by a periodic cosine potential instead of a harmonic spring, has been discussed in Ref.…”
Section: The Modelmentioning
confidence: 99%
“…The resulting probability flux can be expressed in terms of a frequency matrix to characterize a non-equilibrium steady-state [22,23]. Importantly, we have obtained a linear relation between the eigenvalue of the frequency matrix and the average velocity of a thermally driven micromachine [21].…”
Section: Introductionmentioning
confidence: 99%
“…For non-equilibrium steady-state situations, however, detailed balance is broken and a probability flux loop exists in a configuration phase space [17][18][19][20]. Recently, the present authors discussed the non-equilibrium * komura@tmu.ac.jp steady-state probability distribution function of a thermally driven three-sphere micromachine and calculated its probability flux in the corresponding configuration space [21]. The resulting probability flux can be expressed in terms of a frequency matrix to characterize a non-equilibrium steady-state [22,23].…”
Section: Introductionmentioning
confidence: 99%